Implementation problems with European Union’s energy system regulations in Central East Europe - Krawczyk, Jan (2009)
RES Master´s Thesis Verkefnið er unnið í tengslum við Háskóla Íslands og Háskólann á Akureyri he 1992 Earth Summit in Rio de Janeiro spearheaded concerns about the environment and the future wellbeing of Earth and human civilization. It highlighted the importance of green energy and sustainable energy development. The European Union’s Council progressed forward, spring boarding off of the environmental concerns and scientific knowledge, to establish and develop regulations, laws and tools to promote green and sustainable energy in Europe. This analysis will focus on the regulations, laws, and directives of the European Union’s primary energy market. It describes the background of the main European Council’s (EC) energy sector regulation documents and analyzes the following: Directive 2006/32/EC on energy end-use efficiency and energy services, Directive 2001/77/EC on the promotion of electricity produced from renewable energy sources in the internal electricity market and Directive 2003/30/EC on the promotion of the use of biofuels or other renewable fuels for transport. This work provides a general overview, highlights the main goals, and reports on the mechanisms, both proposed and in effect, used to reach these established goals. Lastly, this thesis will investigate the penalty system, or lack thereof, and discuss the difficulties in measuring its results. The implementation of these directives is discussed for a representative sample of three Central Eastern Europe countries, specifically the Slovak Republic, the Czech Republic, and Poland. New European Union Member States have different markets, economical situations, energy sources, and supplies. This work will analyze the energy sector in terms of renewable energy, energy efficiency, and biofuels market. It shows the targets for each country and the forecasts concerning energy production. Finally, an overview of the energy policies needed to reach the goals will be presented, along with conclusions as to whether it will be possible or not to achieve the ...